Faktor-Faktor yang Mempengaruhi Motivasi Mahasiswa dalam Mengikuti Perkuliahan Pendidikan Agama Islam pada Perguruan Tinggi Umum di Kabupaten Jember Tahun 2005: Factors Influencing Students’ Motivation to Attend Islamic Religious Education Lectures at Public Universities in Jember Regency in 2005 - Kasman Kasman (LP2M Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2006)
Low student motivation to attend Islamic Religious Education (PAI) lectures at public universities is a critical issue that may hinder the achievement of national education goals in shaping faithful and pious personalities. Drawing on learning motivation theory, factors influencing motivation stem from three sources: students themselves, the environment, and lecturers' pedagogical engineering. This study aims to identify significant factors affecting student motivation and to develop a predictive model of that motivation. The study employed an analytical survey with 100 students from Jember State University and Muhammadiyah University of Jember, and the data were analyzed using multiple regression. The results showed that, collectively, all three factors significantly influence motivation, but individually only the pedagogical engineering factor was significant, with the regression model Y = -2.68 + 0.143X. Furthermore, the sub-factors of using rewards and punishments and organizing the classroom to activate students proved to be the most dominant. In conclusion, lecturers are advised to enhance motivation by providing rewards and implementing active learning strategies in the classroom. Rendahnya motivasi mahasiswa dalam mengikuti perkuliahan Pendidikan Agama Islam (PAI) di perguruan tinggi umum menjadi fenomena krusial yang berpotensi menghambat pencapaian tujuan pendidikan nasional dalam membentuk kepribadian beriman dan bertakwa. Berdasarkan teori motivasi belajar, faktor-faktor yang mempengaruhi motivasi berasal dari tiga aspek: diri mahasiswa, lingkungan, dan rekayasa pedagogis dosen. Penelitian ini bertujuan mengidentifikasi faktor-faktor signifikan yang mempengaruhi motivasi mahasiswa serta menemukan model prediksi motivasi tersebut. Metode yang digunakan adalah pendekatan survei analitis dengan sampel 100 mahasiswa dari Universitas Negeri Jember dan Universitas Muhammadiyah Jember, dianalisis menggunakan regresi berganda. Hasil penelitian menunjukkan bahwa secara bersama-sama ketiga faktor berpengaruh signifikan, namun secara individual hanya faktor rekayasa pedagogis dosen yang signifikan dengan model regresi Y = -2,68 + 0,143X. Lebih lanjut, sub-faktor pemberian hadiah dan hukuman serta pengorganisasian kelas untuk mengaktifkan mahasiswa terbukti paling dominan. Kesimpulannya, dosen disarankan meningkatkan motivasi melalui pemberian penghargaan dan strategi pembelajaran aktif di kelas.